Some paradoxes and inadequacies in the management of science and technology in Vietnam - Quang, Huynh; Ly, Nguyen Hong (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2021)
On the basis of practical arguments, the article reflects the paradoxes and inadequacies that are barriers to the development of science and technology in Vietnam. The article's authors used methods of information collection, analysis, comparison and inference to prove and clarify the arguments, and at the same time identify the causes of paradoxes, inadequacies and related problems. Finally, with the method of analyzing and summarizing experience, the authors propose solutions to remove barriers and create motivation for science and technology to develop more. Code: 21050602